Media Education and Brazilian Educational Policies for the Enhancement of Learning - Siqueira, Alexandra Bujokas de; Rothberg, Danilo [UNESP] (Grupo Comunicar, 2014)
As media education concepts and practices have been disseminated and strengthened in European countries and Americas, the policies responsible for that expansion remain little known, particularly in countries where the achievements have been recently noted. That is the case for Brazil, where there have been new opportunities for media education, considered as a valuable resource to help accomplish goals of the educational system. This paper looks into the contribution of media education to the enhancement of teaching and learning in the context of innovations brought by recent policies of the Brazilian Ministry of Education. After educational reform programmes which brought the opportunity for emerging fields such as media education, we produced teaching material and conducted a series of workshops with students and teachers from state secondary schools. By reading and producing multimedia information about local public services available to young people, pupils learned about democracy, citizenship, civic engagement, media language, and identity. Lessons from our experiment are discussed against the backdrop of education policies being implemented to ameliorate harsh conditions resulting from the recent economic crisis. We suggest that media education can help by creating a learning environment in which the students become aware of the value of educational attainments.
Keywords: Media education; public policies; digital inclusion; teachers training; media literacy; multimodality; education policies